2016
DOI: 10.1016/j.ijrobp.2016.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Cells Surviving Exposure to Proton or Photon Radiation Share a Common Immunogenic Modulation Signature, Rendering Them More Sensitive to T Cell–Mediated Killing

Abstract: Purpose This study was designed to provide the foundation for combining immunotherapy to induce tumor antigen-specific T cells with proton radiation therapy to exploit the activity of those T cells. We have recently defined “immunogenic modulation,” a mechanism distinct from immunogenic cell death, whereby tumor cells surviving photon radiation therapy nonetheless become more susceptible to cytotoxic T lymphocyte (CTL)-mediated lysis. However, to our knowledge, there are no prior studies examining the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 33 publications
(42 reference statements)
3
102
0
Order By: Relevance
“…This increased PD-L1 expression significantly increased the chordoma cells' sensitivity to avelumab-mediated ADCC of NK cells (Figure 3D). In a previous study we observed that radiation did not modulate PD-L1 expression on tumor cell lines [44]. Similarly, chordoma cell lines (JHC7, UM-Chor1, U-CH2, and MUG-Chor1) exposed to 8 Gy radiation showed no increase in PD-L1 expression after 72 h (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 67%
“…This increased PD-L1 expression significantly increased the chordoma cells' sensitivity to avelumab-mediated ADCC of NK cells (Figure 3D). In a previous study we observed that radiation did not modulate PD-L1 expression on tumor cell lines [44]. Similarly, chordoma cell lines (JHC7, UM-Chor1, U-CH2, and MUG-Chor1) exposed to 8 Gy radiation showed no increase in PD-L1 expression after 72 h (Supplemental Table 1).…”
Section: Discussionmentioning
confidence: 67%
“…3) is supported by published in vitro studies showing an upregulation of these tumor-associated antigens in multiple non renal cell carcinoma cell lines following ionizing radiation (13, 37). Similarly, the tumor-associated antigen CA9 was found to be elevated following SBRT in our study (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…A growing body of evidence has also demonstrated that sublethal doses of radiation can induce expression of calreticulin and CD80, leading to increased cytotoxic lymphocyte activity following irradiation of tumor cells (1214). Preclinical tumor models and in vitro data utilizing other tumor types have revealed that radiation therapy can increase TAA expression (13, 15). While RCC appears resistant to conventional fractionated radiation therapy (16), recent publications have shown that high doses delivered with modern stereotactic body radiation therapy (SBRT) can produce local control with limited toxicity (17, 18).…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of patients with various cancers with low CALR expression responded less well to inducers of immunogenic cell death than patients with high CALR expressing tumours (65). Cells from a variety of cancers that have survived exposure to radiation express more cell surface CALR and this was associated with an enhanced sensitivity to cytotoxic T-cell killing (66). CD166 antigen (ALCAM), that was consistently up-regulated in this study, is an immunoglobulin receptor that binds to the CD6 T-cell differentiation antigen.…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%